Determination of dimenhydrinate and cinnarizine in combined dosage form in presence of cinnarizine impurity - Abdelwahab, Nada Sayed; Abdelrahman, Maha Mohammed; Salama, Fathy Mahmoud; Ahmed, Amal Badawy (European Journal of Chemistry, 2015)
Three accurate, sensitive and time saving spectrophotometric methods have been developed and validated for determination of mixture of dimenhydrinate (DMH) and cinnarizine (CIN) in presence of cinnarizine impurity (1-(diphenylmethyl)piperazine) (IMP). In method A; dimenhydrinate was determined by measuring 1D amplitudes at 292.0 nm while cinnarizine and its impurity were determined by 1DD method at 256.2 and 219.6 nm, respectively, using standard spectrum of 20 µg/mL of dimenhydrinate as a divisor. Method B depends on dividing spectrum of ternary mixture by standard spectrum of 20 µg/mL of dimenhydrinate and then cinnarizine and its impurity were determined in the obtained ratio spectrum by ratio difference method using the difference between 219.0 and 237.2 nm and between 230.0 and 264.0 nm, respectively. On the other hand dimenhydrinate could be determined by dividing spectrum of ternary mixture by standard spectrum of 20 µg/mL of cinnarizine and then it were determined at the obtained ratio spectrum by ratio difference method using the difference between 216.8 and 232.8 nm. Method C is the mean cantering of ratio spectra method (MCR) where the amplitudes at 234.8, 240.0 and 233.6 nm in the second mean centering ratio spectra were used for determination of dimenhydrinate, cinnarizine and its impurity, respectively. The developed methods were validated according to ICH guidelines regarding good accuracy and precision, and they were successfully applied to pharmaceutical formulation and laboratory prepared mixtures. The results were statistically compared with those obtained by reported method and no significant difference was found.